The Role of Bonus Mechanism in Moderating Transfer Pricing Determinants: Supporting SDG 16 on Transparent Institutions - Kiswanto Kiswanto; Rahmawati Rahmawati; Aidy Yudha Prastyanto (Journal of Current Studies in SDGs, 2027)
Objective: To examine the role of bonus mechanisms in moderating the effects of tax management, intangible assets, and debt covenants on transfer pricing decisions. The study highlights the importance of transparent corporate governance and responsible financial practices in supporting Sustainable Development Goal (SDG) 16, particularly regarding accountable institutions and transparent reporting. Method: The study employed a quantitative approach with hypothesis testing using companies listed on the Indonesia Stock Exchange during the 2016–2019 period. Using purposive sampling, 122 observation units were obtained. Data were collected from annual reports and financial statements, while hypothesis testing was conducted using path analysis with IBM SPSS Amos 24. Results: The results indicate that tax management and debt covenants have a positive and significant effect on transfer pricing, while intangible assets have a negative and significant effect on transfer pricing. Furthermore, the bonus mechanism significantly moderates the relationship between tax management and transfer pricing. However, the bonus mechanism does not moderate the effects of intangible assets and debt covenants on transfer pricing. Novelty: Contributing by incorporating the bonus mechanism as a moderating variable to explain how managerial incentives influence transfer pricing decisions. The findings provide implications for strengthening corporate accountability, tax governance, and transparent financial practices aligned with SDG 16.